If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x(2+11x)=
We move all terms to the left:
3x(2+11x)-()=0
We add all the numbers together, and all the variables
3x(11x+2)-()=0
We add all the numbers together, and all the variables
3x(11x+2)=0
We multiply parentheses
33x^2+6x=0
a = 33; b = 6; c = 0;
Δ = b2-4ac
Δ = 62-4·33·0
Δ = 36
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$\sqrt{\Delta}=\sqrt{36}=6$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(6)-6}{2*33}=\frac{-12}{66} =-2/11 $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(6)+6}{2*33}=\frac{0}{66} =0 $
| 15b-5b=10b | | r-10=-10-r | | 0.2(d–8)=0.3d+7–5+0.5d | | 2x+7=5×-5 | | (3x-4)^2+16=0 | | 9y+2=6y+17 | | 150m-125m+42750=45450-200m | | -d-8=8-d | | (x-1)(x-5)=x+4x | | 7x+3=- | | 9x+5=-121 | | 6x+27=x^2 | | 22x^2-126x+169=0 | | -v/6=37 | | (W+9)(w-7)=0 | | x+3/4=2 | | 6(n-4)=8 | | 6(m+2)=4 | | 4x=13x | | n-2(n-5)=-10n-(2-3n) | | 15x=5x+7 | | 1/3+2x/5=8/15 | | -5+6=12w+62 | | 4x(x+4)=-15 | | 5(3x-2x)=30 | | -15+45=-3(x+1) | | -x=6x-14 | | x-37=22 | | 3(x+1)-5=5x-2(3+x) | | 2x-6+6=0 | | -3(x+5)-4=-28 | | 29-2x=3 |